Development of Moodle-Based Teaching Modules to Improve Students' Basic Competencies in the Subject of Electric Motor Installation for Class XI of SMKN 7 Surabaya - Reja Diki Pradana; Subuh Isnur Haryudo; Fendi Achmad; Yulia Fransisca (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to develop and evaluate the effectiveness of a Moodle-based teaching module to enhance students' basic competencies in the Electrical Motor Installation subject for Grade XI at SMKN 7 Surabaya. The research was motivated by low student motivation and learning outcomes due to the limited use of interactive learning media. The study employed the ADDIE development model with a mixed-methods approach, combining qualitative and quantitative analysis. Validation was conducted by content and assessment experts, followed by limited implementation in classroom settings. The results indicate that the module was highly feasible, with expert validation scores averaging above 80%. Student responses reflected high practicality, with an average score of 86.76%. Effectiveness was assessed through comparisons between pre-test and post-test scores, showing a significant improvement with an average N-Gain score of 0.80, categorized as high. In conclusion, the Moodle-based teaching module is feasible, practical, and effective in improving students' understanding and skills in Electrical Motor Installation learning.